2019
DOI: 10.1016/j.bbr.2018.08.003
|View full text |Cite|
|
Sign up to set email alerts
|

Hippo/YAP signaling pathway mitigates blood-brain barrier disruption after cerebral ischemia/reperfusion injury

Abstract: Ischemia/reperfusion (I/R) injuries commonly lead to breakdown of the blood-brain barrier (BBB). Restoration of the BBB can relieve neurologic damage caused by I/R injuries. The Hippo/YAP signaling pathway mediates cell proliferation, regulated cell death, and differentiation in various organisms and has been shown to participate in the restoration of the heart after I/R. In this study, we investigated whether the Hippo/YAP pathway plays a role in I/R injury in brain, especially in regard to I/R-induced BBB br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…Similarly, our study suggests that YAP/TAZ actively participates in endothelial activation that could occur under pathophysiological conditions such as inflammation. In line with this, the role of Hippo/YAP signaling in regulation of blood-brain barrier after cerebral ischemic/reperfusion injury was recently demonstrated [ 36 ]. Although, further studies are needed to determine whether YAP/TAZ is involved in endothelial activation induced by other inflammatory stimuli, it is notable that YAP/TAZ could play a key role in not only physiological angiogenic responses, but also pathological endothelial inflammation.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, our study suggests that YAP/TAZ actively participates in endothelial activation that could occur under pathophysiological conditions such as inflammation. In line with this, the role of Hippo/YAP signaling in regulation of blood-brain barrier after cerebral ischemic/reperfusion injury was recently demonstrated [ 36 ]. Although, further studies are needed to determine whether YAP/TAZ is involved in endothelial activation induced by other inflammatory stimuli, it is notable that YAP/TAZ could play a key role in not only physiological angiogenic responses, but also pathological endothelial inflammation.…”
Section: Discussionmentioning
confidence: 74%
“…[106][107][108][109] Besides neurotrophin signaling, interestingly, the pathway-based analysis revealed that these miRNAs act on pathways known to be altered in ischemic conditions and involved in neuroprotection, such as TNF, Hippo, and PI3K. [110][111][112] Among the miRNAs targets here identified, supposed to be downregulated in our model, we highlighted several genes involved in apoptosis and inflammation processes.…”
Section: Discussionmentioning
confidence: 99%
“…BBB disruption is a hallmark of stroke and a mediator of CIRI and stroke progression (45). Restoration of the BBB can relieve neuronal damage caused by CIRI (46). Our findings demonstated that CTs could suppress the activation of MAPK signalings in neurons.…”
Section: Discussionmentioning
confidence: 99%